Public space in urban Asia - Lim, William Siew Wai, 1932- (World Scientific, 2014)
"The world faces two absolute imperatives. One is to eradicate global poverty and reduce the income gap. The other is to ensure social and environmental sustainability. There is currently an increasing convergence of views among the majority, particularly the younger generation, that to achieve these goals we need to redefine key concepts such as inclusiveness and bottom up participation. Over the last few decades the rise of many cities, especially in emerging economies, has threatened to erode much of public space. It is in this context that William SW Lim, Chairperson of the Asian Urban Lab has edited Public Space in Urban Asia, to discuss the issue of Public Space in selected Asian cities"--